Study on costing techniques in garments accessories sector of Bangladesh Shore to Shore (BD) Limited - Chowdhury, Sajjadul Hoq (BRAC University, 2014)
This internship report is submitted in a partial fulfillment of the requirements for the degree of Bachelor of Business Administration,2013.